What is the normal value of the neutrophil-to-lymphocyte ratio?. (December 2017) - Forget, Patrice; Khalifa, Céline; Defour, Jean-Philippe; Latinne, Dominique; Pel, Marie-Cécile; Kock, Marc
Abstract Background Neutrophil-to-lymphocyte ratio (NLR) has proven its prognostic value in cardiovascular diseases, infections, inflammatory diseases and in several types of cancers. However, no cut-off has been proposed on the basis of reference values coming from healthy population. Methods Routine blood samples were obtained (n = 413) from workers (age: median 38, range: 21–66 years) involved in a health care prevention program, to determine means, standard deviations (SDs), 95% confidence intervals (95% CI), percentiles P2.5 and P97.5. A second independent sample of healthy volunteers is compared (n = 29). Results The mean NLR is 1.65 [±1.96 SD: 0.78–3.53] (95% CI [0.75–0.81] and [3.40–3.66]). In the second cohort (healthy control), the NLR values are in the same range, whichever the used analyzer. No NLR assessed in the validation series is out of the proposed limits. Conclusions We have identified that the normal NLR values in an adult, non-geriatric, population in good health are between 0.78 and 3.53. These data will help to define the normal values of the NLR.